Copepod Lipidomics: Fatty Acid Substituents of Structural Lipids in Labidocerca aestiva, a Dominant Species in the Food Chain of the Apalachicola Estuary of the Gulf of Mexico - Paul L. Wood; Stan C. Kunigelis (Life)
Zooplanktonic copepods represent a major biological mass in the marine food chain that can be affected by climate change. Monitoring the health of this critical biomass is essential for increasing our understanding of the impact of environmental changes on marine environments. Since the lipidomes of marine organisms are known to adapt to alterations in pH, temperature, and availability of metabolic precursors, lipidomics is one technology that can be used for monitoring copepod adaptations. Among the key lipid parameters that can be monitored are the fatty acid substituents of glycerolipids and glycerophospholipids. We utilized high-resolution tandem mass spectrometry (≤2 ppm mass error) to characterize the fatty acid substituents of triacylglycerols, glycerophosphocholines, ceramides, and sphingomyelins of Labidocerca aestiva. This included monitoring for furan fatty acid substituents, a family of fatty acids unique to marine organisms. These data will contribute to establishing a lipid database of the fatty acid substituents of essential structural lipids. The key findings were that polyunsaturated fatty acids (PUFAs) were only major substituents in glycerophosphocholines with 36 to 44 carbons. Triacylglycerols, ceramides, and sphingomyelins contained minimal PUFA substituents. Furan fatty acids were limited to mono- and di-acylglycerols. In summary, we have built a baseline database of the fatty acid substituents of key structural lipids in Labidocerca aestiva. With this database, we will next evaluate potential seasonal changes in these lipid substituents and long-term effects of climate change.